Meninas e meninos: construção das identidades de gênero em crianças de dois anos - Sentís, Maria Dolly Paula Martín (2018)
This work presents results of a research carried out in a full-time public Child Education Center in João Pessoa, Brazil, with a group of 2-year-old children. The objective was to identify the emergence of gender manifestations in children through their behaviors and interactions. Data collection included interviews with the educators and classroom observation. The text, located in the field of Cultural Studies, approaches the notions of identity and culture from this perspective, as well as the main psychological theories aiming at emphasizing the importance of the study of this age group in regard of the appearance of gender constructions in the imaginary of children and the reproduction of social roles. The research shows the different factors that contribute to the formation of gender identity in the daily life of the day care center, but also conceives the child as a subject that must be recognized in the investigation, implying a work with children and not about them. The results show how education has a normalizing tendency; nevertheless, children transgress. The study contributes to rethinking child education as a decisive step on the way to shaping gender identities and moving towards a new educational model with gender equality as a priority in education policies.